Characterization and application of nanostructured films containing Au and TiO2 nanoparticles supported in bacterial cellulose - Dal'Acqua, Nicolle; Mattos, Alessandra Batista de; Krindges, Israel; Pereira, Marcelo Barbalho; Barud, Hernane da Silva [UNESP]; Lima Ribeiro, Sidney Jose [UNESP]; Silva Duarte, Gian Carlos; Radtke, Claudio; Almeida, Luciano Costa; Giovanela, Marcelo; Crespo, Janaina da Silva; Machado, Giovanna (Amer Chemical Soc, 2015)
In the last several years, the use of renewable energy sources has increased; consequently, the number of studies regarding their efficiency has also increased. It is well known that fossil and atomic fuels will not last forever and that their use contributes to environmental pollution. Thus, nanostructured thin films have attracted attention due to numerous applications, including construction of photovoltaic energy generating and photoluminescence materials. Therefore, in this study, we prepared and characterized thin films supported on bacterial cellulose that were produced using the layer-by-layer (LbL) technique. The weak polyelectrolytes, such as poly(allylamine hydrochloride) (PAH) and poly(acrylic acid) (PAA), combined with titanium dioxide (TiO2) and gold nanoparticles (Au NPs) were used to produce flexible devices capable of producing hydrogen gas (H-2) by photocatalysis. The presence of the Au NPs and TiO2 in the films was confirmed using UV-vis spectroscopy, Rutherford backscattering spectrometry, and X-ray diffraction. Scanning electron microscopy was used to evaluate the surface morphology of the films, and the distribution and average size of the Au NPs were analyzed using transmission electron microscopy, which revealed sizes in the nanometer range. Finally, the thin films were analyzed using gas chromatography to evaluate the H-2 production by photocatalysis. Overall, the system with (PAH + TiO2) and PAA solutions at pH = 4.0 in the presence of gold salt that were reduced with ultraviolet light were more efficient due to their greater interactions with the TiO2 during multilayer deposition.